2016
DOI: 10.3791/52409
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Drug-Induced Renal Hemodynamic Dysfunction Using Sonographic Technology in Rats

Abstract: The kidney normally functions to maintain hemodynamic homeostasis and is a major site of damage caused by drug toxicity. Drug-induced nephrotoxicity is estimated to contribute to 19-25% of all clinical cases of acute kidney injury (AKI) in critically ill patients. AKI detection has historically relied on metrics such as serum creatinine (sCr) or blood urea nitrogen (BUN) which are demonstrably inadequate in full assessment of nephrotoxicity in the early phase of renal dysfunction. Currently, there is no robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Current clinical diagnostic methods mainly rely on the measurement of serum creatinine (CR) and blood urea nitrogen (BUN), which are insensitive and incapable of accurately diagnosing AKI at the early stage as obvious changes in the levels of CR and BUN can only occur at the loss of about 75% of functional nephrons. 10 Though traditional imaging methods such as computed tomography, 11 magnetic resonance imaging, 12 and ultrasound imaging 13 have been useful for AIK diagnosis mainly via noninvasive in vivo imaging of the changes in anatomy and histology of the kidneys, the lack of detecting AKI-associated biomarkers at the molecular level has impeded the ability for the early diagnosis of AKI. Recently, molecular optical imaging 14−18 that allows high sensitivity, low cost, and facile operation has shown promise for AKI diagnosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Current clinical diagnostic methods mainly rely on the measurement of serum creatinine (CR) and blood urea nitrogen (BUN), which are insensitive and incapable of accurately diagnosing AKI at the early stage as obvious changes in the levels of CR and BUN can only occur at the loss of about 75% of functional nephrons. 10 Though traditional imaging methods such as computed tomography, 11 magnetic resonance imaging, 12 and ultrasound imaging 13 have been useful for AIK diagnosis mainly via noninvasive in vivo imaging of the changes in anatomy and histology of the kidneys, the lack of detecting AKI-associated biomarkers at the molecular level has impeded the ability for the early diagnosis of AKI. Recently, molecular optical imaging 14−18 that allows high sensitivity, low cost, and facile operation has shown promise for AKI diagnosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the present study, the increase of RI was parallel with the increase of serum creatinine after the third day of infusion. In another study on mice, the renal RI precedes the serum creatinine in a diagnosis of AKI after cisplatin infusion (12). However, there are some limitations for using RI in the diagnosis of all kidney diseases because it is affected by other hemodynamic disorders rather than in kidney as well as the difficulty of measuring RI without sedation of dogs which affected on its measurement (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can differentiate transient from persistent AKI in critically ill patients (10,11). Recently, it was reported that an increase in the renal RI is an accurate and sensitive tool for early prediction of AKI in rats (12).…”
Section: Introductionmentioning
confidence: 99%
“…Renal blood flow measurement with noninvasive Doppler ultrasound. Pulse-wave Doppler ultrasound was performed at the Cardiovascular Physiology Core at Brigham and Women's Hospital as previously described (40). Briefly, all animals were acclimatized overnight before experimental procedures were performed.…”
Section: Methodsmentioning
confidence: 99%